The Influence of Implementation of Management Information Systems on the Quality of Human Resources with Competence as an Intervening Variable Regional Finance, Revenue and Asset Management Agency (BPKPAD) Binjai City - Ananda Vagita Lubis, Vina; Farida Ferine, Kiki (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of implementing management information systems on the quality of human resources with competence as an intervening variable. This research was conducted at the Office of the Regional Financial, Revenue and Asset Management Agency (BPKPAD) in Binjai City. The population of this study was 173 employees. Sampling was carried out using the Slovin formula so that a sample of 121 employees was obtained. The type of research used is associative quantitative. This research model uses path analysis, and the measurement tool uses Smart PLS version 3.3.3. The results of this study are. Competence has a positive and significant impact on HR quality. Management Information Systems have a positive and significant impact on competence. The Management Information System has a positive and significant effect on HR Quality. The Management Information System has a positive and significant effect on HR Quality through Competence.